Composition and strain engineered AgNbO3-based multilayer capacitors for ultra-high energy storage capacity. Issue 15 (1st April 2021) - Zhu, Li-Feng; Zhao, Lei; Yan, Yongke; Leng, Haoyang; Li, Xiaotian; Cheng, Li-Qian; Xiong, Xiangming; Priya, Shashank
Abstract : With strain engineer and MnO2 addition, an ultra-high energy-storage density W rec = 7.9 J cm −3 and efficiency η = 71% were achieved in Ag(Nb0.85 Ta0.15 )O3 + 0.25 wt% MnO2 multilayer capacitors. Abstract : Antiferroelectric (AFE) materials owing to their double-loop-shaped electric-field ( E ) dependent polarization ( P ) are considered quite promising for energy-storage capacitors. Among the large family of AFE materials, the AgNbO3 composition is attractive not only because it is environmentally friendly, but also because it has high recoverable energy storage density ( W rec ). However, the reported values of W rec < 4 J cm −3 in Ag(Nb0.85 Ta0.15 )O3 multilayer capacitors are lower than that of the corresponding monolithic ceramic. This is attributed to high leakage current density ( J ) and inferior breakdown strength (BDS) in multilayer structures. Here we demonstrate that MnO2 doping not only effectively reduces the J value and results in slim P – E loops, but also enhances the breakdown strength (BDS). Multilayer capacitors with composition Ag(Nb0.85 Ta0.15 )O3 + 0.25 wt% MnO2 (ANT + Mn) demonstrated an excellent W rec = 7.9 J cm −3 and efficiency η = 71%. Extensive investigations were conducted on ANT + Mn multilayer capacitors to demonstrate the role of strain engineering in enhancing the maximum polarization ( P max ) and Δ P values. Results reveal the effect of built-in stress in the active layers of multilayer capacitors on the magnitude of P max, remanent polarization ( P r ) and W rec, and provide guidance towards the development of high energy storage density in multilayer capacitors.